The research of pharmacokinetic parameters and metabolism of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4h-1,2,4-triazol-3-yl)thio)acetate for use in military and civilian medicine - D. L. Usenko; B. O. Varynskyi; O. I. Panasenko; L. P. Morozova; O. P. Shmatenko; A. M. Solomennyi (Український журнал військової медицини)
Introduction. Chromatographic methods are often used in the study of pharmacokinetic parameters. Thus, the aim of the study was to investigate the pharmacokinetic parameters and metabolism of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (ASP) as a potential active pharmaceutical ingredient with high rates of proven acto- and stress-protective effects, which can be recommended for use in military and civilian medicine.